THE PSYCHOLOGY OF FAKE NEWS: ACCEPTING, SHARING, AND CORRECTING MISINFORMATION - Kiraz, Ersel (Ege Üniversitesi, 2025)
The Psychology of Fake News: Accepting, Sharing, and Correcting Misinformation explores the psychological mechanisms behind the acceptance, dissemination, and rectification of fake news. Written by Rainer Greifeneder, Mariela Jaffe, Eryn Newman, and Norbert Schwarz, the book provides a comprehensive analysis of how cognitive biases, social dynamics, and media environments contribute to the spread of misinformation. It delves into the reasons individuals accept false information, the motivations behind sharing such content, and strategies for correcting inaccuracies effectively. By combining theoretical insights with practical recommendations, the book serves as a valuable resource for understanding and combating the pervasive issue of misinformation in the digital age.

The Psychology of Fake News: Accepting, Sharing, and Correcting Misinformation başlıklı eser, sahte haberlerin bireyler ve toplum üzerindeki etkilerini psikolojik bir perspektifle ele almaktadır. Kitap, sahte haberlerin kabul edilme nedenlerini, paylaşım süreçlerini ve yanlış bilgilerin nasıl düzeltilebileceğini inceleyen kapsamlı bir çalışma sunmaktadır. Rainer Greifeneder, Mariela Jaffe, Eryn Newman ve Norbert Schwarz’ın katkılarıyla hazırlanan bu eser, günümüz dijital çağında bilgi kirliliğinin yayılımını anlamak ve çözüm yolları geliştirmek adına hem akademik hem de uygulamalı bir rehber niteliğindedir. İnceleme, kitabın bireylerin bilişsel süreçlerine odaklanarak yanıltıcı bilgilere karşı savunma mekanizmaları geliştirme önerilerini ve bilimsel temellerini detaylı bir şekilde irdelemektedir.
SAHTE HABER PSİKOLOJİSİ: SAHTE HABERLERİN KABULÜ, PAYLAŞILMASI VE DÜZELTİLMESİ
Keywords: Journalism; Gazetecilik [EN] Journalism Studies; Gazetecilik Çalışmaları [EN] Communication Studies; İletişim Çalışmaları [EN] Social Media Studies; Sosyal Medya Çalışmaları [EN] Social Media Applications and Analysis; Sosyal Medya Uygulamaları ve Analizi